issue of developing Digital economy of Mongolia - Badamdorj Batkhishig (Proceedings of the Mongolian Academy of Sciences)
In the first part of the article, the author compares various definitions of digital economy and spells out his own version of its essence and content. He defines digital economy as one of the models of new economy based on digital technology system. The author believes that digital technology system consists of various technologies, such as Big Data, high-speed wireless Internet, blockchain, cloud computing, Internet of things, artificial intelligence, 3D printing, virtual reality and others.